Chinese ink-promoted co-assembly synthesis of 3D hierarchically structured and porous MoCx/C nanocomposites for highly efficient hydrogen evolution reaction. (December 2020) - Fan, Xueliang; Zhang, Hongbin; Gao, Boxu; Lu, Haiyang; Zheng, Luyao; Yang, Xue; Zhang, Yahong; Gao, Qingsheng; Tang, Yi
Abstract: To explore high-performance carbide catalysts for hydrogen evolution reaction (HER), the rational design of hierarchically porous catalyst benefitting active-site exposure and fast mass transport is extremely demanded. Herein, Chinese ink (CI), used for writing and drawing for thousands of years, is adopted to promote the formation of co-assembly of carbon nanoparticles and Mo-based lamellar organic-inorganic hybrids, which, after pyrolysis in Ar atmosphere, is further converted to 3D hierarchically structured and porous MoCx /C nanocomposites (HSP-MoCx /C) for high-efficient HER. Their skeleton structure, porosity, carbon amounts, phase composition and active species dispersity are well modulated by simply tuning the CI dosage in starting mixture, and its mechanism is monitored via a series of physicochemical characterization techniques. The optimal composite exhibits remarkable HER activity with low overpotentials of 112 and 86 mV at current density of 10 mA cm −2, and the small Tafel slopes of 52 and 50 mV dec −1 in 0.5 M H2 SO4 and 1 M KOH solution, respectively. Such performance stems from the combined effects of enhanced ion/mass transport, abundant exposed active sites and high conductivity due to the 3D hierarchically skeleton architecture of catalysts. This work paves a new strategy to design hierarchically porous materials for chemical conversion and energy storage. Graphical abstract: Image 1